Effectiveness of Plant-Based Diets in Regression of Coronary Atherosclerosis - Manesha Juriasinghani, Monica Punshi, Ramsha Tehreem, Bakhtawar Kousar, Bilal Karim, Mahreen Bhatti, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: In spite of the medical therapy developed, coronary atherosclerosis is still theprimary cause of cardiovascular morbidity. Recent data indicate that vegetarian dietaryhabits can also be used to promote vascular recovery and enhance metabolic risk factors.